Shape memory properties of interpenetrating polymer networks (IPNs) based on hyperbranched polyurethane (HBPU). (15th January 2020) - Wang, Cong; Zhang, Yaoming; Li, Jianming; Yang, Zenghui; Wang, Qihua; Wang, Tingmei; Li, Song; Chen, Shoubing; Zhang, Xinrui
Graphical abstract: Highlights: Hyperbranched polyurethane was applied through grafting epoxy resin to obtain interpenetrating polymer networks. Crosslinking network points help enhancing thermal and mechanical properties. All interpenetrating polymer networks express excellent shape memory effect. Abstract: In this article, a type of hyperbranched polyurethane (HBPU) with triazine structure was successfully synthesized. Afterwards, HBPU was applied through grafting epoxy resin (EP) to fabricate the interpenetrating polymer networks (IPNs) with different ratio of HBPU/EP. The structure of HBPU prepolymer and the formation of the HBPU/EP IPNs were characterized and confirmed by Nuclear Magnetic Resonance (NMR) and Fourier Transform Infrared (FTIR) spectroscopy, and the nanoscale phase separation in IPNs composite was analyzed by Atomic Force Microscope (AFM). Besides, the thermal and mechanical results indicated that the IPNs structure enables the material with high strength and thermal stability. Shape memory cycles test demonstrated that the HBPU/EP INPs possess an excellent shape memory performance, and the best shape fixity and recovery were presented by IPNs composite with 20 wt% HBPU.